Green Synthesis, Characterization of Zinc Oxide Nanoparticles and their Incorporation into Glass Ionomer Cement for Inhibition of Streptococcus mutans - Ahalya, N.; Dhamodhar, P.; Vaishnavi, A.D. (Asian Journal of Chemistry, 2021)
In present study, zinc oxide nanoparticles were synthesised using Syzygium aromaticum and characterized using UV visible spectroscopy, SEM, XRD and FTIR techniques. The characteristic hexagonal structure of the ZnO nanoparticles was confirmed through XRD analysis. The UV-Visible spectrum showed a strong absorbance at 366 nm confirming the presence of ZnO and the peak at 496 cm-1 in FTIR indicated the Zn-O stretch bond. Average size of the zinc oxide nanoparticles obtained from SEM analysis was found to be 86 nm. The zinc oxide nanoparticles exhibited better antibacterial activity than clove extract, when tested against clinical isolates of Streptococcus mutans. The nanoparticles incorporated into the dental restorative material, glass ionomer cement (GIC) were tested against S. mutans and exhibited better antibacterial activity than clove extract. Glass ionomer cement (GIC) did not exhibit antibacterial activity alone, but the incorporation of ZnO nanoparticles into GIC significantly improved antibacterial activity. Hence, ZnO embedded GIC is a promising material in restorative dentistry for preventing the recurrence of dental caries.